Pemanfaatan Media Pembelajaran Pinball untuk Meningkatkan Hasil Belajar Siswa Kelas IX SMPN 1 Dolopo Madiun - 'Aena, Alisa Qorry; Warsini, Warsini; Wardoyo, Arif; Yudono, Kristophorus Divinanto Adi (DIDAKTIS : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research aims to examine the effectiveness of using pinball learning media in improving the learning outcomes of class IX students at SMPN 1 Dolopo Madiun, explaining how pinball learning media can influence students' motivation and interest in learning, determining the extent to which pinball learning media can be integrated into the learning process to improve the quality of teaching. and understanding of the material, and providing recommendations for the use of interactive learning media to support improving student learning outcomes. The results showed that the student's average score in writing descriptive text was 78 in cycle 1. After using pinball media in cycle 2, the student's average score increased to 84. In cycle 3, by evaluating and using pinball media again, the average student in writing descriptive text reaches 90. Thus, the use of pinball learning media can significantly improve student learning outcomes, especially in writing descriptive text. Based on observations and evaluations carried out during the research, there was an increase in student participation and motivation in the learning process. Students are more enthusiastic and active in understanding the lesson material presented through pinball learning media. Apart from that, the results of the learning evaluation show an increase in the average student score after implementing this media. These findings indicate that pinball learning media is effective in creating a pleasant learning atmosphere and encouraging students to better understand the subject matter.